Strategi Pengembangan Ternak Sapi Potong untuk Meningkatkan Pendapatan Petani Kabupaten Manokwari, Papua Barat - Anari, Oktovianus; Suryahadi, Suryahadi; Pandjaitan, Nora Herdiana (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
Manokwari District is the base of raising beef cattle, and the production of seeds, feed, livestockproduction facilities.This activity production facilities strongly supports the achievement of good beef cattle productivity.The objectives of the research were (1) to identify factors influencing the development of beef cattle business, (2) to establish the scale of beef cattle and appropriate marketing and (3) to develop alternative strategy of beef cattle business development for improvement income of farmers of Manokwari District.Processing and data analysis used: (1) External Factor Evaluation (EFE) andInternal Factor Evaluation (IFE), (2) external internal (IE) matrix; (3) Strengths, Weaknesses, Opportunities, Threats (SWOT); and (4) Quantitative Strategic Planning Matrix (QSPM) analysis. Determination of priority strategies with QSPM, based on the results of alternative strategies resulting from the SWOT matrix. Based on the calculation of QSPM matrix, there are three strategic priorities that can be implemented, namely (1) strengthening the capital to compete, (2) expanding the market share of beef cattle, and (3) improving the quality of beef cattle.